JAK2 mutation may predict response and guide first line treatment in rheumatoid arthritis - Yasmin Adel; Mohamed Sabry; Amr Mohamed El-Sabbagh; Yousra Sadeq (SpringerOpen, 2021)
Abstract Background JAK (Janus kinase) inhibitors work by inhibiting the activity of one or more of the enzyme Janus kinase with a therapeutic application for treatment of cancer and inflammatory disorders such as rheumatoid arthritis (RA). We aimed to study impact of JAK2 mutation in serum of rheumatoid arthritis patients on response to first line with conventional synthetic disease-modifying anti-rheumatic drug (csDMARDS) at 3rd month by evaluating DAS28 and ACR response criteria. The study included 85 newly diagnosed rheumatoid arthritis patients and 50 matched controls. Basal JAK2 mutation assessed by PCR in blood samples, TNF-α and IL 6 were measured by ELISA in serum of patient and control groups. All patients started therapy with csDMARDs. Response assessment at 3rd month was evaluated by DAS28 and ACR response criteria. JAK2 mutation was correlated with different clinical and laboratory parameters of patients. Results Seventeen females (83.5%) and 14 males (16.5%) with age mean ± SD (years); (48.7 ± 7.2). Pretreatment JAK2 mutation, TNF-α and IL 6 were significantly high in patients. JAK2 mutation was detected in 45 (52.9%) patients while 40 (47.1%) patients were JAK2 non-mutant. Mutant JAK2 was significantly linked to severity of disease evaluated by DAS28; 14 (70%) of patients with DAS28 (≤ 2.6) were non-mutant JAK2 vs sex (30%) patients mutant JAK2 while 19 (73.1%) of patients with DAS28 (> 5.1) were mutant JAK2 vs 7 (26.9%) patients non-mutant JAK2 (P 0.02). JAK2 mutation found to be significantly correlated with ACR 20, 50, and 70 response criteria; 68.2% of patients with non-mutant JAK2 showed ACR 70 vs 31.8% in mutant group, 52% of patients with non-mutant JAK2 showed ACR 50 vs 48% in mutant group while 31.6% of patients with non-mutant JAK2 showed ACR 20 vs 68.4% in mutant group (P 0.02). JAK2 mutation were more presented in young age patients (mean ± SD; 47.1 ± 7.2 vs 50.4 ± 6.9 in mutant vs non-mutant JAK2 patients, respectively with P 0.03). JAK2 mutation was associated with high pretreatment TNFα and IL6 level in serum. Mean ± SD of TNFα; 49.4 ± 41.9 in mutant vs 26 ± 24.4 pg/ml in non-mutant group, with P (0.003) while mean ± SD of IL6; 83.5 ± 56.8 in mutant vs 47 ± 46.9 pg/ml in non-mutant group, with P (0.002). Conclusions Adult RA with pretreatment JAK2 mutation significantly showed high disease activity and high pretreatment TNFα and IL6 levels. Patients with JAK2 mutation found to be linked to poor response to 1st line csDMARDs including MTX so they could get more benefit with early introduction of JAK inhibitors as first line monotherapy or when combined with csDMARDS especially those with moderate to severe active RA. Trial registration Institutional Research Board (IRB)-Faculty of Medicine: IRB Proposal Code: R.20.11.1075-2020/11/16. Clinicaltrials.gov registration date: 8/12/2020, code: NCT04667988 .